2004
DOI: 10.1177/097168580401000207
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Values: A Study of Future Professionals

Abstract: Values represent the basic convictions that a specific mode of conduct or end-state of existence is personally or socially preferable to an opposite or converse mode of conduct or end state of existence. 1 Kluckhohn conceptualized values as principles for action encompassing abstract goals in life and modes of conduct that an individual prefers across contexts and situations. 2 Schwartz defined values as desirable, trans-situational goals, varying in importance that serves as guiding Perception of Values: A St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 24 publications
1
31
0
5
Order By: Relevance
“…Kothari et al (1998) too had reported team spirit and punctuality as the values perceived by teachers of technomanagement education. In another study, Parashar et al (2004) reported that both postgraduate as well as undergraduate students of professional studies had perceived team spirit and patriotism as existing values, thus, falling in line with the fi ndings of the present study wherein teachers happen to be in agreement with the students. Discipline, duty, respect, trustworthiness, equity and worship have been perceived exclusively by vegetarian teachers as existing values.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…Kothari et al (1998) too had reported team spirit and punctuality as the values perceived by teachers of technomanagement education. In another study, Parashar et al (2004) reported that both postgraduate as well as undergraduate students of professional studies had perceived team spirit and patriotism as existing values, thus, falling in line with the fi ndings of the present study wherein teachers happen to be in agreement with the students. Discipline, duty, respect, trustworthiness, equity and worship have been perceived exclusively by vegetarian teachers as existing values.…”
Section: Resultssupporting
confidence: 84%
“…Perhaps the expectation is to see peace as a major terminal value-a destination where all routes converge. In a study of postgraduate and undergraduate students of professional studies, Parashar et al (2004) had found that all such students expected peace and justice as ought to be variables. The fi ndings of the present study, therefore, reveal common expectations of teachers and are taught in terms of these two values.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A theme emerging from the literature is that personal values affect human perception and behaviour because they contain a judgement element in which they formulate social norms and emotions about what is right, good or desirable (Hemingway 2005;Parashar et al 2004). The following table exhibits some important value definitions which emphasize the function of value as motivations for behaviour, attitude, and action (Table 1).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Rokeach (1973), well-known as the first scientist who raised the theory about different kinds of values, believed that there are two kinds of values: instrumental values and terminal values. Although some scientists want to re-assess some parts of the Rokeach value theory, such as a value concept (Jemna & Curelaru, 2009), structure of values (Braithwaite, 1982;Schwartz & Bilsky, 1987) and value survey (Braithwaite & Law, 1985;Parashar, Dhar, & Dhar, 2004), but his two kinds of value theory has been almost accepted broadly.…”
Section: Values and Value Systemsmentioning
confidence: 99%